Evaluation strategies of the student learning process during the new normality (Revista Innova Educación, 2022)
The COVID-19 pandemic accelerated the realization of classes through virtual platforms and made the teacher evaluation, instead of positively reflecting the level of knowledge, evidenced a low performance of the students, in this case, of the Preparatory No. 7 of the Autonomous University of Guerrero, Mexico. To explain this problem, qualitative research was carried out with descriptive and interpretative scope. 50 students were interviewed, and a structured questionnaire with ten open-ended questions was developed. The main results indicated that students perceive that traditional assessment does not reflect their knowledge, but incipient learning, stress and anxiety, so they suggested modifying the assessment process.
Keywords: learning; virtual classes; strategies; traditional evaluation